Lyrical ecphrasis and lyricography as a form of artistic knowledge in the face of the impossibility of a single interpretation of symbols: the case of Alberti-Miró in the poetry collection Maravillas con variaciones acrósticas en el jardín de Miró - Calderón Aguirrezabala, José Luis (Escritura e Imagen, 2025)
As a result of Antonio García Berrio's theories on Miró's language, who addressed the impossibility of a single interpretation of his symbols, and who published with Teresa Hernández the poetics of the visual arts Ut poesis pictura, the lyrical ekphrasis written by Rafael Alberti in his collection of poems Maravillas con variaciones acrósticas en el jardín de Miró is proposed here as a form of artistic knowledge of the Catalan artist's pictorial corpus, precisely because it is a text written by the poet-painter, who was a good knower of the work of the painter-poet. Just in the 50th anniversary of the publication of the first edition of this collection of poems, illustrated with Miró's lithographic work, and the exhibition on the lyricographies and graphic poems of the Cadiz-born poet held at the Rafael Alberti Foundation in 2025, the second edition of this collection of poems is particularly noteworthy, as Miró's lithographs were replaced by illustrations by Rafael Alberti himself, complementing his own ekphrases and imitating the pictorial language of the artist being honoured in a text-image symbiosis in the style of the lyrical graphics that the poet had begun to create in 1945.
Keywords: Rafael Alberti; Joan Miró; description; ekphrasis; symbols; lyricography; poetry-painting; Antonio García Berrio